Pengaruh Harga dan Citra Merek Terhadap Keputusan Pembelian Pada Konsumen Mie Gacoan Kota Baru Jambi - Adinda Riani Putri; Putri, Adinda Riani; Ningsih, Putri Apria (Manajemen Keuangan Syariah, 2025)
The culinary industry is experiencing rapid development, especially fast food restaurants that use noodles as their main ingredient, one of which is the famous Mie Gacoan. This study aims to determine the extent to which price and brand image influence the purchasing decisions of consumers of Mie Gacoan, Kota Baru Branch, Jambi. This study uses a quantitative approach with a questionnaire method, where questionnaires are distributed to 100 consumers of Mie Gacoan. Data analysis was carried out using SPSS version 26.0, with the data analysis method using multiple linear regression. The results of the study indicate that the T test (partially) price has a significant negative effect on purchasing decisions, with a Tcount value (-5.680)> Ttable (1.988) and a significance value of 0.000<0.05, and partial image also has a significant effect on purchasing decisions with a Tcount value (7.273)> Ttable (1.988) and a significance value of 0.000<0.05. Based on the F test (simultaneously), price and image significantly influence purchasing decisions with a calculated F value (47.414) > F table (3.09) and a significance value of 0.000 <0.05. Therefore, it can be concluded that both partially and simultaneously, price and brand image influence purchasing decisions. Based on the Adjusted R Square (R2) value, which means that consumer purchasing decisions are influenced by price and brand image, it has an influence of 48.4%, and the remaining 51.6% is influenced by other variables not examined in this study. Keywords: Price, Brand Image, Purchasing Decisions